Mapping CPTED parameters with the LookCrim application - Sani, Ana Isabel (2021)
Crime prevention through environmental design (CPTED) is a multi-disciplinary approach to deterring criminal behavior through environmental design. CPTED strategies rely upon the influence on offender decisions that precede criminal acts by affecting the built, social, and administrative environment. We introduce an innovative technological tool, the LookCrim application, based on CPTED’s principles, to assess characteristics of specific physical spaces. This article describes the developed web platform and mobile app tools and their functional overview and explores some opportunities and challenges, such as the integration in smart cities, and ethical and legal issues. The LookCrim application gathers geo-tagged information enriched with CPTED characteristics—natural surveillance, natural access control, territorial reinforcement and maintenance, organized by categories defined by the European Committee for Standardization. The LookCrim application may be useful for organized data acquisition on urban spaces to develop empirical studies that will support environmental urban design decisions.